Medawar and the immunological paradox of pregnancy: in context. Issue 1 (14th December 2020) - Male, Victoria
Abstract: In 1953, Peter Medawar defined 'the immunological paradox of pregnancy', whereby the semi-allogeneic foetus can survive for 9 months in its mother, while a semi-allogeneic graft would be rejected. Here, I revisit the immunological paradox of pregnancy, setting it in the context of the time in which it was proposed. I go on to examine the extent to which Medawar's ideas on the subject have stood the test of time and how they have shaped reproductive immunology.